2007
DOI: 10.1158/1078-0432.ccr-07-1104
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Heat Shock Protein 90 in Pancreatic Cancer Impairs Insulin-like Growth Factor-I Receptor Signaling, Disrupts an Interleukin-6/Signal-Transducer and Activator of Transcription 3/Hypoxia-Inducible Factor-1α Autocrine Loop, and Reduces Orthotopic Tumor Growth

Abstract: Purpose: Inhibitors of heat-shock protein 90 (Hsp90) may interfere with oncogenic signaling pathways, including Erk, Akt, and hypoxia-inducible factor-1a (HIF-1a). Because insulin-like growth factor-I receptor (IGF-IR) and signal transducer and activator of transcription 3 (STAT3) signaling pathways are implicated in the progression of pancreatic cancer, we hypothesized that blocking Hsp90 with geldanamycin derivates [17-allylamino-geldanamycin (17-AAG), 17-(dimethylaminoethylamino)-17-demethoxygeldanamycin (1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
119
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 134 publications
(124 citation statements)
references
References 43 publications
3
119
0
2
Order By: Relevance
“…Inhibitory effects on other growth factor signals have also been implicated, for example, IGF-1R (Lang et al, 2007b) and Kit (Bauer et al, 2006). We found that the reduced proliferation and radiosensitising effects of Hsp90 inhibition in oesophageal cancer cell lines correlated with a decrease in growth factor-induced signalling.…”
Section: Discussionmentioning
confidence: 56%
“…Inhibitory effects on other growth factor signals have also been implicated, for example, IGF-1R (Lang et al, 2007b) and Kit (Bauer et al, 2006). We found that the reduced proliferation and radiosensitising effects of Hsp90 inhibition in oesophageal cancer cell lines correlated with a decrease in growth factor-induced signalling.…”
Section: Discussionmentioning
confidence: 56%
“…Results showed that knockdown of PFKFB3 not only reversed the enhanced aerobic glycolysis but also inhibited tumor cell proliferation and migration. The potential mechanisms of how IL-6 upregulates PFKFB3 are that IL-6 increases the expression of HIF-1 and HIF-1 activates transcription of PFKFB3 (29). However, what is the concrete mechanism of how IL-6 exerts its tumor promoting effect by regulating the PFKFB3 in CRC is still under further consideration.…”
Section: Pfkfb3 -------------------------mentioning
confidence: 99%
“…3, CAU-CAAACAAGAACUUCCUACACCA; UGGUGUAGGAA-GUUCUUGUUUGAUG) and Lipofectamine (Invitrogen; ref. 43). For experiments using stealth RNAi, sole administration of Lipofectamine to the culture medium served as a control.…”
Section: Real-time Pcr For Klf5 Survivin and Pdgf-a Expressionmentioning
confidence: 99%